Innovation and Practice of Collaborative Education Models for Water Engineering Majors under the Background of Digital Transformation - Li, Feng (Journal of Educational Research and Policies, 2025)
With the development of the digital economy and the increasing demand for informatization in the water engineering industry, the cultivation of water engineering professionals faces new challenges. This paper analyzes the current development trends in the water engineering industry and the impact of the digital economy on the talent competency structure, proposing a multidisciplinary talent training model centered on university-industry collaboration. By constructing a multidisciplinary curriculum system, strengthening practical teaching, promoting deep collaboration between universities and enterprises, and applying digital technologies, this study explores pathways to cultivate talent that meets the demands of the new era, providing a reference for the reform of higher education in water engineering.